Indigenous organic resources utilization, application methods and sowing time replenish soil nitrogen and increase maize yield and total dry biomass. (8th November 2022) - Imran, Imran; Amanullah, Amanullah; Al Tawaha, Abdel Rahman
Abstract: Wise management of indigenous resources replenishes soil nutrients and improves crop productivity and soil sustainability. Three year consecutive experiments were performed in the framework of Farmers Field School (FFS) during 2012–2014. Organic nitrogen sources [animal-urine (AU), animal-manures (AM), and animal manure-compost (AMC) with two application methods [interior-application method (IAM) and exterior-application method (EAM)] and three sowing timing [early sowing (ES), late-sowing (LS), and timely sowing (TS)] were studied. One control plot in each replication was placed as a check. The results showed that among different sowing time, TS has higher grains year −1, 1000 grains weight, dry biomass, grain yield and harvest index (HI) than LS and ES. AM delayed silking and physiological maturation. A higher grains year −1, 1000 grains weight, grain yield, total dry biomass, and HI were observed with AMC than control plots. In application methods, the IAM has delayed the silking and physiological maturity as compared to EAM. Similarly, higher grains year −1, 1000 grains weight, grain yield, dry biomass, and HI were observed with IAM than EAM. In sowing timing, higher grain nitrogen (GN) was observed in TS. Higher GN produced by AMC and AU treated plots. AMC produced 10% higher GN than manures treated plots. The IAM produced higher GN than EAM. The AMC produced significantly higher soil N and statistically at par with AU treated plots. IAM applied AMC, maize grain yield was higher than the AU and AM. In conclusion, AMC and AU embedded in soil with TS can sustainably increase maize yield and soil productivity.